PENGARUH VARIASI KUAT ARUS LAS LISTRIK PADA PENGELASAN BAJA C45 DENGAN SUDUT KAMPU V GANDA TERHADAP UJI TARIK DAN UJI IMPAK - Tirto tirto (Universitas Harapan Medan, 2019)
The development of the era and technology in the field of advanced construction can not be separated from the welding because welding has an important role in the engineering and reparation of metal. In terms of welding welding power is influenced by arc voltage, current, welding speed, magnitude of penetration and electrical polarity. various types of appliances that can be used, generally the most widely used electric welding in the usage.penggunaan variations of electric current can be easily set according to the type of welding materials and welding methods on welding machine listrikk.baja which is in use also various types, times this I will gun steel c45, karna on steel machining world c45 many in use on the engine shaft